The Ballseye programme: a mixed-methods programme of research in traditional sexual health and alternative community settings to improve the sexual health of men in the UK - Claudia Estcourt; Lorna Sutcliffe; Catherine H Mercer; Andrew Copas; John Saunders; Tracy E Roberts; Sebastian S Fuller; Louise J Jackson; Andrew John Sutton; Peter J White; Ruthie Birger; Greta Rait; et al. (Programme Grants for Applied Research, 2016)
Background: Sexually transmitted infection (STI) diagnoses are increasing and efforts to reduce transmission have failed. There are major uncertainties in the evidence base surrounding the delivery of STI care for men. Aim: To improve the sexual health of young men in the UK by determining optimal strategies for STI testing and care Objectives: To develop an evidence-based clinical algorithm for STI testing in asymptomatic men; model mathematically the epidemiological and economic impact of removing microscopy from routine STI testing in asymptomatic men; conduct a pilot randomised controlled trial (RCT) of accelerated partner therapy (APT; new models of partner notification to rapidly treat male sex partners of people with STIs) in primary care; explore the acceptability of diverse venues for STI screening in men; and determine optimal models for the delivery of screening. Design: Systematic review of the clinical consequences of asymptomatic non-chlamydial, non-gonococcal urethritis (NCNGU); case–control study of factors associated with NCNGU; mathematical modelling of the epidemiological and economic impact of removing microscopy from asymptomatic screening and cost-effectiveness analysis; pilot RCT of APT for male sex partners of women diagnosed with Chlamydia trachomatis infection in primary care; stratified random probability sample survey of UK young men; qualitative study of men’s views on accessing STI testing; SPORTSMART pilot cluster RCT of two STI screening interventions in amateur football clubs; and anonymous questionnaire survey of STI risk and previous testing behaviour in men in football clubs. Settings: General population, genitourinary medicine clinic attenders, general practice and community contraception and sexual health clinic attenders and amateur football clubs. Participants: Men and women. Interventions: Partner notification interventions: APTHotline [telephone assessment of partner(s)] and APTPharmacy [community pharmacist assessment of partner(s)]. SPORTSMART interventions: football captain-led and health adviser-led promotion of urine-based STI screening. Main outcome measures: For the APT pilot RCT, the primary outcome, determined for each contactable partner, was whether or not they were considered to have been treated within 6 weeks of index diagnosis. For the SPORTSMART pilot RCT, the primary outcome was the proportion of eligible men accepting screening. Results: Non-chlamydial, non-gonococcal urethritis is not associated with significant clinical consequences for men or their sexual partners but study quality is poor (systematic review). Men with symptomatic and asymptomatic NCNGU and healthy men share similar demographic, behavioural and clinical variables (case–control study). Removal of urethral microscopy from routine asymptomatic screening is likely to lead to a small rise in pelvic inflammatory disease (PID) but could save > £5M over 20 years (mathematical modelling and health economics analysis). In the APT pilot RCT the proportion of partners treated by the APTHotline [39/111 (35%)], APTPharmacy [46/100 (46%)] and standard patient referral [46/102 (45%)] did not meet national standards but exceeded previously reported outcomes in community settings. Men’s reported willingness to access self-sampling kits for STIs and human immunodeficiency virus infection was high. Traditional health-care settings were preferred but sports venues were acceptable to half of men who played sport (random probability sample survey). Men appear to prefer a ‘straightforward’ approach to STI screening, accessible as part of their daily activities (qualitative study). Uptake of STI screening in the SPORTSMART RCT was high, irrespective of arm [captain led 28/56 (50%); health-care professional led 31/46 (67%); poster only 31/51 (61%)], and costs were similar. Men were at risk of STIs but previous testing was common. Conclusions: Men find traditional health-care settings the most acceptable places to access STI screening. Self-sampling kits in football clubs could widen access to screening and offer a public health impact for men with limited local sexual health services. Available evidence does not support an association between asymptomatic NCNGU and significant adverse clinical outcomes for men or their sexual partners but the literature is of poor quality. Similarities in characteristics of men with and without NCNGU precluded development of a meaningful clinical algorithm to guide STI testing in asymptomatic men. The mathematical modelling and cost-effectiveness analysis of removing all asymptomatic urethral microscopy screening suggests that this would result in a small rise in adverse outcomes such as PID but that it would be highly cost-effective. APT appears to improve outcomes of partner notification in community settings but outcomes still fail to meet national standards. Priorities for future work include improving understanding of men’s collective behaviours and how these can be harnessed to improve health outcomes; exploring barriers to and facilitators of opportunistic STI screening for men attending general practice, with development of evidence-based interventions to increase the offer and uptake of screening; further development of APT for community settings; and studies to improve knowledge of factors specific to screening men who have sex with men (MSM) and, in particular, how, with the different epidemiology of STIs in MSM and the current narrow focus on chlamydia, this could negatively impact MSM’s sexual health. Funding: The National Institute for Health Research Programme Grants for Applied Research programme.